Do Religious Factors Impact Armed Conflict? Empirical Evidence from Sub-Saharan Africa - Matthias Basedau; Georg Strüver; Johannes Vüllers; Tim Wegenast (German Institute of Global and Area Studies (GIGA), 2011)
Theoretically, the 'mobilization hypothesis' establishes a link between religion and conflict by arguing that religious structures such as overlapping ethnic and religious identities are prone to mobilization; once politicized, escalation to violent conflict becomes likelier. Yet, despite the religious diversity in sub-Saharan Africa and the religious overtones in a number of African armed conflicts, this assumption has not yet been backed by systematic empirical research on the religion-conflict nexus in the region. The following questions thus remain: Do religious factors significantly impact the onset of (religious) armed conflict? If so, do they follow the logic of the mobilization hypothesis and, if yes, in which way? To answer these questions, this paper draws on a unique data inventory of all sub-Saharan countries for the period 1990-2008, particularly including data on mobilization-prone religious structures (e.g. demographic changes, parallel ethno-religious identities) as well as religious factors indicating actual politicization of religion (e.g. inter-religious tensions, religious discrimination, incitement by religious leaders). Based on logit regressions, results suggest that religion indeed plays a significant role in African armed conflicts. The findings are compatible with the mobilization hypothesis: Overlaps of religious and ethnic identities and religious dominance are conflict-prone; religious polarization is conflict-prone only if combined with religious discrimination and religious tensions.
Keywords: 300; armed conflict; religion; sub-Saharan Africa; mobilization